The Influence of Brand Awareness and Brand Image on the Purchase Decision of Mie Gacoan - Muhyidin Muhyidin; Muhammad Mukhbir; Muhammad Sholahuddin (Institut Agama Islam Al-Fatimah Bojonegoro, 2025)
This study examines the growing popularity of Mie Gacoan in Pasuruan. In the highly competitive culinary industry, strong brand awareness and a positive brand image are critical in capturing consumer attention. The research aims to investigate how these two factors influence consumer purchasing decisions in the region, offering strategic insights for brand development in a dynamic culinary market. The study employs a sample of 100 respondents selected using the accidental sampling technique. Data analysis includes descriptive analysis as well as simultaneous and partial tests conducted using IBM SPSS Statistics 25. The results reveal that both brand awareness and brand image have a positive and significant effect on purchasing decisions, both partially and simultaneously, with an F-value of 342.244 and a significance level of 0.000. These findings indicate that consumers with high brand awareness are more likely to choose Mie Gacoan over competing brands, while a positive brand image contributes to repeat purchasing decisions. This study recommends enhancing brand awareness through creative marketing campaigns and strengthening brand image through product innovation to sustain competitiveness in the culinary market